Study of the Concept of Educational Research Methodology: Research Problem, Variables, Literature Review and Hypothesis - Fitri Wahyuningsih; Nana Sepriyanti; Martin Kustati (Journal Informatic, Education and Management (JIEM), 2026)
Islamic Education research faces fundamental methodological problems, where its four main pillars, namely problem formulation, variables, literature review, and hypothesis, still often adopt secular research paradigms without adequate adaptation. This causes the research to lose its Islamic authenticity. This study uses a qualitative approach with the type of library research . The data analysis techniques used are qualitative content analysis and conceptual analysis . The results of the study show that: 1). Authentic research problems are that research problems in Islamic education are formulated by identifying gaps between Islamic values ​​(Tawhid, Maqashid Sharia ) and the empirical reality of Muslim education. Authentic problems arise from the intersection of normative criticism and field observations. 2). Variable Ontology is that theocentric variables (such as sincerity, piety) are operationalized through a hybrid model that combines behavioral indicators (observed) and spiritual indicators (psychometrics) to maintain their conceptual validity without reducing meaning. 3). Naqli-aqli integration is that the literature review is constructed through the integration of three models: confirmation (naqli and aqli agree), correction (naqli criticizes aqli), and construction (the synthesis of the two gives birth to a new theory). This builds a solid and contextual theoretical foundation. 4). Reflective hypothesis is that the hypothesis is formulated as a bridge that unites normative premises (from naqli) with empirical assumptions (from aqli) in a deductive framework (from general principles to specific assumptions) and inductive (testing through data). The findings of this study can be implemented through the preparation of operational guidelines for Islamic education research methodology that contain a complete framework of the four key elements. This guideline contains practical procedures for formulating problems based on the gap between Islamic values ​​and reality, a hybrid theocentric variable operationalization model, a naqli-aqli integrative literature review template , and the formulation of reflective hypotheses.